The Impact of Digital Technology on Employees' Development via Informal Learning Approach: A Systematic Review - Ke Ma (Adult Education Research Conference, 2024)
The objective of this literature study is to assess the feasibility of HRD practitioners incorporating digital technology to support informal learning in enterprises, with the aim of improving employees' professional development.
Keywords: informal learning; digital technology; training & amp; development; workforce development